2003
DOI: 10.1136/bmj.326.7387.477
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility, acceptability, and effectiveness in primary care of routine telephone review of asthma: pragmatic, randomised controlled trial

Abstract: Objective To determine whether routine review by telephone of patients with asthma improves access and is a good alternative to face to face reviews in general practices. Design Pragmatic, randomised controlled trial. Setting Four general practices in England. Participants 278 adults who had not been reviewed in the previous 11 months. Intervention Participants were randomised to either telephone review or face to face consultation with the asthma nurse. Main outcome measures Primary outcome measures were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 12 publications
(15 reference statements)
4
87
0
4
Order By: Relevance
“…Telephone consultations have been shown in a randomised controlled trial to achieve higher rates of participation in routine asthma reviews than the traditional method of face-to-face reviews. 149 But a large proportion of patients declined to take part in the trial, calling into question the generalisability of the findings to routine practice. In a subsequent implementation study, 150 Pinnock and colleagues compared three forms of asthma review service: a structured recall system in which patients were contacted up to three times by post or by memo issued with repeat prescriptions, and offered the choice of a telephone or a face-to-face review, then followed up opportunistically if they did not make an appointment; a similar recall system (but with no opportunistic follow-up) in which patients were offered only a face-to-face review; and usual care, in which there was no systematic recall.…”
Section: Understanding Processesmentioning
confidence: 99%
“…Telephone consultations have been shown in a randomised controlled trial to achieve higher rates of participation in routine asthma reviews than the traditional method of face-to-face reviews. 149 But a large proportion of patients declined to take part in the trial, calling into question the generalisability of the findings to routine practice. In a subsequent implementation study, 150 Pinnock and colleagues compared three forms of asthma review service: a structured recall system in which patients were contacted up to three times by post or by memo issued with repeat prescriptions, and offered the choice of a telephone or a face-to-face review, then followed up opportunistically if they did not make an appointment; a similar recall system (but with no opportunistic follow-up) in which patients were offered only a face-to-face review; and usual care, in which there was no systematic recall.…”
Section: Understanding Processesmentioning
confidence: 99%
“…Only about a third of people with asthma heed this advice and attend their general practice for a routine annual review [3,4]. Our trial of telephone consultations for asthma demonstrated that telephone-based care can facilitate delivery of routine healthcare, substantially increasing the proportion of patients reviewed when compared with traditional faceto-face consultations [5]. We aimed to explore the preferences expressed by people with asthma for alternative modes of consultation in order to gain insight into factors which may influence the …”
Section: Introductionmentioning
confidence: 99%
“…Modern forms of communication offer considerable potential for enhancing medical care [1][2][3], particularly in ensuring timely access to emergency advice [4,5], and in the management of chronic disease [6,7]. Mobile phones are now widely available [8], and offer innovative opportunities for messaging which have been used to remind patients of appointments [9] and to encourage compliance with inhaled steroids in asthma [10].…”
Section: Introductionmentioning
confidence: 99%